2006
DOI: 10.2307/30035554
|View full text |Cite
|
Sign up to set email alerts
|

Developing Automaticity in Multiplication Facts: Integrating Strategy Instruction with Timed Practice Drills

Abstract: Automaticity in math facts has been of considerable interest to special educators for decades. A review of the intervention literature suggests at least two common approaches to developing automaticity in facts. One is grounded in the use of strategies for teaching facts, the other emphasizes the use of timed practice drills. Recent research indicates that students might benefit from an integration of these two approaches. This experimental study contrasted an integrated approach (i.e., strategies and timed pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
120
0
28

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(153 citation statements)
references
References 38 publications
5
120
0
28
Order By: Relevance
“…Matematik yetersizliğine sahip akıcılık problemleri yaşayan bireylerde sistematik alıştırma ve akıcılık çalışmaları kritik ölçüde önemlidir (Cates ve Rhymer, 2003;Chiesa ve Robertson, 2000;McGlaughlin, Knoop, ve Holliday, 2005;Woodward, 2006). Woodward'a (2006) göre yeni bilgileri elde etme ve unutmama doğrudan doğruya bilgilere cevap verme fırsatları ve öğrenciye verilen alıştırma uygulamalarını sayısıyla bağlantılıdır.…”
Section: Introductionunclassified
See 3 more Smart Citations
“…Matematik yetersizliğine sahip akıcılık problemleri yaşayan bireylerde sistematik alıştırma ve akıcılık çalışmaları kritik ölçüde önemlidir (Cates ve Rhymer, 2003;Chiesa ve Robertson, 2000;McGlaughlin, Knoop, ve Holliday, 2005;Woodward, 2006). Woodward'a (2006) göre yeni bilgileri elde etme ve unutmama doğrudan doğruya bilgilere cevap verme fırsatları ve öğrenciye verilen alıştırma uygulamalarını sayısıyla bağlantılıdır.…”
Section: Introductionunclassified
“…Woodward'a (2006) göre yeni bilgileri elde etme ve unutmama doğrudan doğruya bilgilere cevap verme fırsatları ve öğrenciye verilen alıştırma uygulamalarını sayısıyla bağlantılıdır. Akıcılık uygulamalarının en önemli yönü öğrencilere daha karmaşık ve zorlayıcı matematiksel işlemlerden önce bu becerilere temel oluşturacak ön koşul niteliğindeki temel işlemlerde akıcılık ve ustalık kazanmalarını sağlamaktır (Chiesa ve Robertson, 2000;McDougall ve Brady, 1998;Woodward, 2006). Basit matematiksel beceriler alıştırmalar sayesinde kalıcı hale gelir ve sonrasında ise ileri seviye matematik becerilerini kazanma imkanı sağlar (Woodward, 2006).…”
Section: Introductionunclassified
See 2 more Smart Citations
“…As well as affecting problem-solving, research has shown that inefficient solving of basic facts depletes resources that are needed for acquiring more advanced computational skills, such as those required for multi-digit sums (Cumming & Elkins, 1999). Weak ability to retrieve arithmetic facts can also impede children's ability to follow mathematical discourse and consequently to understand concepts that are introduced in class, such as equivalence, the commutative property and other concepts that form the basis of more advanced mathematics, such as algebra (Gersten, Jordan, & Flojo, 2005;NMAP, 2008;Woodward, 2006).…”
Section: Introductionmentioning
confidence: 99%